THE EFFECT OF THE QUANTITY OF FERTILIZERS ON THE CHEMICAL COMPOSITION OF WINE VARIETIES - Malikov Azim Nematovich; Abdurahmanov Obidjon Khamidovich; Lapasov Sayfiddin Sanakulovich (Scholar Express Journals, 2021)
This article consider the study of the effect of the quantity of fertilizers on the chemical composition of wine varieties
Keywords: The quantity of fertilizers, chemical composition, wine varieties